Strengthening Badan Usaha Milik Desa (BUMDes) Branjang Based on Local Culture (Indonesian Journal of Devotion and Empowerment, 2022)
Community service aims to map cultural potential and public awareness to develop local culture. The service method used is socialization and training. The target audience is the directors and administrators of village-owned enterprises and POKDARWIS managers. The results show that the target community can understand local culture and its mapping for cultural existence. Village-owned enterprises are still at the pilot level, so it is appropriate if the potential mapping results can be used as material for making relevant business unit decisions. Local village culture is included in the main priority of developing BUMDes to extend its business continuity. It means that it is not only short-term orientation but also long-term oriented. The village has several superior cultures, such as woven bamboo, palm sugar, and reog. So far, the community has been very enthusiastic about developing these three cultures. The indicator of the success of the service program can be seen from the cognitive aspect in mapping the village's potential. Suggestions for the village government in the form of financial support and non-financial support in developing village-owned enterprises. The management itself must be loyal and committed to developing BUMDes so that it can bring benefits to the village community. Tujuan pengabdian kepada masyarakat pemetaan potensi budaya dan penyadaran masyarakat untuk mengembangkan budaya local. Metode pengabdian yang digunakan adalah sosialisasi dan pelatihan. Khalayak sasarannya adalah direktur dan pengurus BUMDes serta pengelola POKDARWIS. Hasil pengabdian menunjukkan masyarakat sasaran dapat memahami konsep budaya local dan pemetaanya untuk eksistensi budaya. Saat ini BUMDes masih pada level rintisan, maka tepat sekali jika hasil pemetaan potensi dapat digunakan sebagai bahan pengambilan keputusan unit bisnis yang sesuai. Budaya local desa dimasukan dalam prioritas utama pengembangan BUMDes sehingga keberlangsungan usahanya akan panjang. Artinya tidak hanya orientasi jangka pendek, akan tetapi berorientasi pada jangka panjang. Ada beberapa budaya unggulan desa seperti budaya anyaman bambu, gula aren, dan reog. Selama ini masyarakat semangat sekali dalam mengembangkan ketiga budaya tersebut. Indikator keberhasilan program pengabdian dapat dilihat dari aspek kognitif dalam melakukan pemetaan potensi desa. saran bagi pemerintah desa berupa dukungan finansial dan dukungan non finansial dalam mengembangkan BUMDes. Pengurus sendiri harus loyal dan komitmen dapat mengembangkan BUMDes sehingga dapat mendatangkan manfaat bagi masyarakat desa.